Literature and Medicine: Literature as a Source of Listening, Empathy and Self-Reflection - Zambaldi, Carla Fonseca (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2020)
Modern times have brought advances in the understanding of diseases, new diagnostic and therapeutic resources and the revolutionary use of technology, allowing the progress of medicine. To cover the complexity of the progress of scientific evidence, medical training has reinforced and privileged scientific knowledge. The investment in the formation of humanistic, language, communication, listening and empathy skills was not equivalent to technical training. Such imbalance has shown losses in the ability of the modern physician to listen carefully, to understand globally and to relate appropriately to his patients. Despite this, initiatives to promote human and integral medicine have emerged and have been maintained in medical schools.